Pengaruh Capital Intensity, Liquidity dan Sales Growth Terhadap Agresivitas Pajak - Fanny Nisadiyanti; Willy Sri Yuliandhari (Institut Bisnis dan Informatika Kesatuan, 2021)
The purpose of this study s to find out the impact of capital intensity, liquidity and sales growth on tax aggressiveness. This study uses a population in the coal mining sub-industry corporate listed on the IDX from 2016 to 2019 period. The sample selection technique used is purposive sampling, 14 coal mining sub-industry corporate were selected and the research period was 4 years. Therefore, as many as 56 samples were obtained in this study. The data analysis method used is panel data regression analysis using EViews 11 software. The results show that capital intensity, liquidity and sales growth affect tax aggressiveness simultaneously. Partially, liquidity has a positive effect on tax aggressiveness, while capital intensity and sales growth do not affect tax aggressiveness.